Financial Sector Assessment Program : Montenegro Financial Infrastructure - World Bank; International Monetary Fund (World Bank, Washington, DC, 2016)
Financial infrastructure is the underlying foundation of a country’s financial system. It comprises all institutions, the rules, and standards of all the systems which enable financial intermediation. The quality of a country’s financial infrastructure determines the efficiency of intermediation, the ability of lenders to evaluate risk and of borrowers to obtain credit, insurance, and other financial products at competitive terms. For instance, the efficient and smooth functioning of the payment, and securities settlement systems facilitates the discharge of financial obligations and the safe transfer of funds across distances and institutions; hence, it support the stability of the financial system. This technical note contains the assessment of the national payment and settlement systems (NPS) infrastructure in Montenegro. The assessment was undertaken in the context of the IMF and World Bank (WB) joint Financial Sector Assessment Program (FSAP) mission to Montenegro during September 1-15, 2015. The assessor was Gynedi Srinivas of the World Bank’s Payment Systems Development Group. The assessor will like to thank the counterparts in Montenegro for their excellent cooperation and hospitality during the mission.